2006
DOI: 10.1186/1471-2261-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae, heat shock proteins 60 and risk of secondary cardiovascular events in patients with coronary heart disease under special consideration of diabetes: a prospective study

Abstract: Background: There have been suggestions of an association between Chlamydia pneumoniae, chlamydial heat shock protein (Ch-hsp) 60 and human heat shock protein (h-hsp) 60 infection sero-status and development of secondary cardiovascular events. Patients with diabetes might be at higher risk since they are prone to infections. The objective of this study was to investigate prospectively the role of Chlamydia pneumoniae (CP), chlamydial heat shock protein (Ch-hsp) 60 and a possible intermediate role of human heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…35,36 Moreover, few studies have investigated the relation between CD14 polymorphism and persistent C pneumoniae infection, anti-cHsp60 antibodies, and stroke. 23,24,37,38 This case-control study was aimed at evaluating the association between CD14 promoter polymorphisms, frequency of persistent C pneumoniae infection, and anti-cHsp60 induction in stroke patients.…”
mentioning
confidence: 99%
“…35,36 Moreover, few studies have investigated the relation between CD14 polymorphism and persistent C pneumoniae infection, anti-cHsp60 antibodies, and stroke. 23,24,37,38 This case-control study was aimed at evaluating the association between CD14 promoter polymorphisms, frequency of persistent C pneumoniae infection, and anti-cHsp60 induction in stroke patients.…”
mentioning
confidence: 99%
“…It has been suggested that chronic infection of Ch. pneumoniae may contribute to the development of CHD by increasing the concentrations of acute phase reactants such as C-reactive protein, heat shock proteins 60, fibrinogen, inflammatory markers such as interleukin7 and sialic acid which are predictors of CHD [18,13,19]. Furthermore, it has been demonstrated an association between Chlamydia lipopolysaccharide-IgA (LPS-IgA) seropositivity and elevated levels of interferon-gamma (IFN-γ), interleukin-10 (IL-10), tumor necrosis factor-alpha (TNF-α), soluble vascular cell adhesion molecule (sVCAM-1) and soluble Eselectin(sE-selectin) in CHD patients that might indicate persistent Chlamydia infection and a proinflammatory state [5,20,21].…”
Section: Introductionmentioning
confidence: 99%